Pengaruh Literasi Keuangan Syariah Terhadap Minat Nasabah Di Bank Sumut Syariah Perdagangan - Yulika Rabania (Yayasan Rahmat Islamiyah, 2022)
This study wa conducted to determine the effect of Islamic financial literacy on constumer of Bank Sumut Syariah Tranding,amouniting to 150. While the samples were 60. The analytical method use was quantitative,namely simple regression analysis. This analysis inculeds, validity test, reliability test,and simple regression. Hytpothesis testing thourg t test, and determination coefficient test (Rsuquare). The results af this study indicate that Islamic financial literacy has a significant effect. This is evidenced by the –t test of financial Literacy T_ hitung 17.606.> t _tabel 1.671, H_o is rejected, meaning that the fiannacial literacy variable has a significant and significant influence on customer interest this is evidience by the significant level of 0.000. The significant level is proven to smaller than the finanacial literacy variable contributes 84.2% to determination is 84. 2% which meants that the financial literacy variable contributes 84.2% to the costumer interest variable. While the remaining 15.08% it can be counceld that H_a there is an effect of Islamic financial literacy (X) on customer interest (Y) at Bank Sumutb Syariah Tranding while H_o No can influcend the Islamic fianancial literacy (X) on customer Interest (Y) in the Bank of North Islamic Trade.